Development and assessment of a formal learning module to educate veterinary students in an intensive care unit about transfusion reactions. Issue 4 (25th June 2020) - Haines, Jillian M.; Wardrop, K. Jane; Lindberg, Christopher J.; Carbonneau, Kira J.; Ngwenyama, Thandeka R.; Martin, Linda G.
Abstract: Objective: To develop and assess the instructional efficacy of an online learning module on transfusion reactions in small animals and to evaluate participants' satisfaction of the module. Design: Randomized controlled trial. Setting: University teaching hospital. Subjects: A total of 55, fourth‐year veterinary students, 27 in a treatment group that received the learning module plus standard rotation training and 28 in a control group (no module) who received only standard training Interventions: Students received a pretest on transfusion reactions followed by administration of a transfusion reaction learning module covering recognition, treatment, prevention, case examples, and self‐assessment questions for 6 common transfusion reactions. Students also received a module satisfaction survey, a post‐test at 2 weeks post‐module, and a retention test at 6 weeks post‐module. Measurements and main results: Previous transfusion medicine exposure did not affect pretest scores and there was no difference in pretest scores between groups. The module group scored higher on the post‐test ( P  < 0.001) and retention test ( P  = 0.002) than the control group. Mean post‐test scores were 74.4% and 57.7% and mean retention test scores were 80.6% and 56.5% for the module and control groups, respectively. The module group scored higher on posttest and retention questions involving reaction recognition ( P  < 0.001). Students were overall very satisfied with the module with an average score of 4.8 (1‐5). Conclusions: A transfusion reaction instructional module can be delivered successfully to veterinary students on an ICU‐based clinical rotation. Students taking the module scored significantly better on post‐assessments up to 6 weeks after module administration as compared to students receiving only conventional clinical rotation training.